1987
DOI: 10.1007/bf00417767
|View full text |Cite
|
Sign up to set email alerts
|

Early rising or delayed bedtime: which is better for a short night's sleep?

Abstract: The present study compares the effects on sleep and the subsequent period of wakefulness of delaying bedtime of 2 h or advancing rising time by 2 h in subjects clearly differentiated by morningness or eveningness in their circadian rhythms. Twelve young healthy good sleepers, six morning types (MT) and six evening types (ET), were selected. The data obtained from the second 24 h (night and day) with delayed bedtime (DB) and advanced rising time (AR) were compared with those obtained in the reference condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The results indicated that there was a distinct difference between both chronotypes: evening types rated lower self-alertness upon waking compared with morning types. 49 Moreover, subjective and objective sleepiness has been shown to be greater in evening-type subjects than in morning-type subjects, especially in the morning. [50][51][52] It is important to note that, in all instruments, questions are predominantly subjective, relating sleep and activity times to a personal "feeling best" rhythm, 1 or asking subjects to assess hypothetical situations (e.g., "Considering only your own feeling best rhythm, at what time would you get up if you were entirely free to plan your day?").…”
Section: Other Aspects Possibly Affecting the Assessment Of Chronotypesmentioning
confidence: 99%
“…The results indicated that there was a distinct difference between both chronotypes: evening types rated lower self-alertness upon waking compared with morning types. 49 Moreover, subjective and objective sleepiness has been shown to be greater in evening-type subjects than in morning-type subjects, especially in the morning. [50][51][52] It is important to note that, in all instruments, questions are predominantly subjective, relating sleep and activity times to a personal "feeling best" rhythm, 1 or asking subjects to assess hypothetical situations (e.g., "Considering only your own feeling best rhythm, at what time would you get up if you were entirely free to plan your day?").…”
Section: Other Aspects Possibly Affecting the Assessment Of Chronotypesmentioning
confidence: 99%